ILLUSTRATION BOOK MEDIA DESIGN DIABETES MELLITUS TYPE 1 IN IKADAR - Pertiwi, Ratih; Asmara, Nur; Wahyudi, Tri; Iriani, Yani (International Journal of Psychosocial Rehabilitation, 2020)
Based on data from the Indonesian Pediatric Association (IDAI) there were more than 1000 cases of children with Type 1 Diabetes Mellitus in 2014. Meanwhile, in 2016 there were an additional 112 new patients. The number of children with diabetes has increased over the past five years. The number increases to 500 percent in children aged 0-18 years. Type 1 diabetes itself is a type of diabetes with low insulin production. People with Type 1 Diabetes require insulin in the form of injections and insulin pumps. Therefore Type 1 Diabetes is also called insulin dependent diabetes, or known as autoimmune diabetics with a cause that is not yet known with certainty. If a child has been exposed to Type 1 Diabetes Mellitus (DM) then he must use insulin therapy for the rest of his life, in addition to setting a healthy lifestyle and eating. Parents or families of new diabeticians must be clever in managing the child’s diet, blood sugar, and activities. This illustrated book media is aimed at parents of new diabeticians who are struggling and feel confused when dealing with Type 1 Diabetes Mellitus for the first time. This illustrated book media is expected to be a guide for parents to be "friend" with Type 1 Diabetes who will become their child’s life partner.